Retrocaval ureter: report of 2 different clinical spectrums - Mohd Ghani @ Mamat, Khairul Asri; Abd Majid, Malinda; Tee, S. C.; Sundram, Murali; Woo, Susan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2014)
Retrocaval ureter is a relatively rare anomaly where ureteric obstruction may occur as a result of ureter passes behind the inferior vena cava (IVC), hence, compressing it between the IVC and the vertebrae. We report 2 cases of retrocaval ureter with different presentations. One patient was managed surgically with minimally invasive approach and the other was managed conservatively.